Effect of nitrogen and potassium on gaseous exchange and biomass distribution in basil (Ocimum basillicum L.) - Combatt C., Enrique; Pérez P., Dario Javier; Jarma-Orozco, Alfredo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Basil is considered a promising plant of recent exploitation in Colombia, but among the limitations for its expansion, counts the implementation of a nutrition plan with the application of nitrogen and potassium, which result in increased and sustainable production. The objective was to evaluate the effect of nitrogen and potassium on the gaseous exchange variables and biomass gain and harvest index (HF) of a basil crop, hybrid Nufar F. This research was carried out under greenhouse conditions in the Faculty of Agricultural Sciences of the University of Córdoba, Colombia. In order to optimize the response variables, a Box Bernard matrix was used, increased to 3 (2k + 2k + 2k + 1 + 1) to obtain the combinations of nitrogen and potassium necessary for this research. Among the gaseous exchange variables evaluated were: the rate of photosynthesis, the stomatal conductance and the internal CO2 concentration. As for the biomass, the dry mass of the roots, stem, and leaves and the harvest index were evaluated. The most relevant results indicated that the maximum rate of photosynthesis (17.3 μmol CO2 m-2 s-1) was observed when applying 190 kg ha-1 N and 12.5 kg ha-1 K, while the stomatal conductance was higher (65.13 mmol CO2 m-2 s-1) with the same dose of N but with doses of 237.5 kg ha-1 of K. The highest value of the dry mass of the roots, stem and leaves was found with the maximum dose of N (190 kg ha-1) although, for potassium, the combinations that promoted the highest accumulation of biomass were differential for the roots, stem and leaves (180.69, 237.5 and 12.5 kg ha-1, respectively).